Wideband Reconfigurable Antenna with Beams Switching for Wireless Systems Applications - Faouzi Rahmani; Naima Amar Touhami; Abdelmounaim Belbachir Kchairi; Nihade Taher (Proceedings, 2020)
In this paper, a new wideband reconfigurable antenna with beams switching for wireless systems applications is presented and studied. The radiation pattern of the proposed antenna can be changed using the PIN diodes. The designed antenna has a bandwidth of 26.75% from 5.31 to 6.95 GHz and can steer the beam in the azimuth plane. The simulated realized gain of the antenna obtained is 5.9 dB at 5.8 GHz. The proposed antenna can operate for various wireless systems, such as Wi-Fi, WiMAX, Intelligent Transportation System (ITS) and C-band satellite. The simulated results are also presented and investigated.